IMF Financial Operations 2018. (International Monetary Fund, 2018)
IMF Financial Operations 2018 provides a broad introduction to how the IMF fulfills its mission through its financial activities. It covers the financial structure and operations of the IMF and provides background detail on the financial statements. It reviews the IMF's three main activities: lending, surveillance, and technical assistance.